Indigenous Self-Determination in Australia Histories and Historiography - Rademaker, Laura; Rowse, Tim (Aboriginal History Monographs, 2020)
Histories of the colonisation of Australia have recognised distinct periods or eras in the colonial relationship: 'protection' and 'assimilation'. It is widely understood that, in 1973, the Whitlam Government initiated a new policy era: 'self-determination'. Yet, the defining features of this era, as well as how, why and when it ended, are far from clear. In this collection we ask: how shall we write the history of self-determination? How should we bring together, in the one narrative, innovations in public policy and Aboriginal and Torres Strait Islander initiatives? How (dis)continuous has 'self-determination' been with 'assimilation' or with what came after? Among the contributions to this book there are different views about whether Australia is still practising 'self-determination' and even whether it ever did or could. This book covers domains of government policy and Indigenous agency including local government, education, land rights, the outstation movement, international law, foreign policy, capital programs, health, public administration, mission policies and the policing of identity. Each of the contributors is a specialist in his/her topic. Few of the contributors would call themselves 'historians', but each has met the challenge to consider Australia's recent past as an era animated by ideas and practices of Indigenous self-determination.